HIV and co‐infections. Issue 1 (16th June 2013) - Chang, Christina C.; Crane, Megan; Zhou, JingLing; Mina, Michael; Post, Jeffrey J.; Cameron, Barbara A.; Lloyd, Andrew R.; Jaworowski, Anthony; French, Martyn A.; Lewin, Sharon R.
Summary: Despite significant reductions in morbidity and mortality secondary to availability of effective combination anti‐retroviral therapy (cART), human immunodeficiency virus (HIV) infection still accounts for 1.5 million deaths annually. The majority of deaths occur in sub‐Saharan Africa where rates of opportunistic co‐infections are disproportionately high. In this review, we discuss the immunopathogenesis of five common infections that cause significant morbidity in HIV‐infected patients globally. These include co‐infection with Mycobacterium tuberculosis, Cryptococcus neoformans, hepatitis B virus, hepatitis C virus, and Plasmodium falciparum . Specifically, we review the natural history of each co‐infection in the setting of HIV, the specific immune defects induced by HIV, the effects of cART on the immune response to the co‐infection, the pathogenesis of immune restoration disease (IRD) associated with each infection, and advances in the areas of prevention of each co‐infection via vaccination. Finally, we discuss the opportunities and gaps in knowledge for future research.